Exercise addiction, muscularity-oriented eating and beliefs about sports nutrition supplements in students who regularly exercise - Sema Arslan Kabasakal (Physical Education of Students, 2024)
Background and Study Aim. Regular exercise has a positive effect on physical, psychological, and social health. However, excessive participation in exercise and the need for compulsive exercise can lead to exercise addiction. This addiction may result in several issues, including injuries, unhealthy eating behaviors, and negative attitudes. To prevent these potential problems, it is important to identify the extent of exercise addiction among individuals who exercise regularly. In this regard the study aims to examine the potential relationships between exercise addiction, muscularity-oriented eating and belief levels in sports nutritional supplements among students.